An interpretative model for the management of contemporary cultural landscapes in linear infrastructure projects - Berte, Elena; Panagopoulos, Thomas; Zanon, Bruno (Journal of Environmental Engineering and Landscape Management, 2013)
Structures and potentialities of cultural landscapes have been studied mostly under a historical perspective. This article questions if contemporary societies can develop cultural landscapes. Starting from an analysis of the structure of contemporary landscapes, it investigates methods of developing cultural landscapes with contemporary knowledge and background. The theoretical assumptions are based on an ecosystem approach and consider the social and functional values in relation to the infrastructure project. Linear infrastructures are the physical basis for material and immaterial links between societies. They structure local territories, but more often reflect upper level rationalities thus physically cross areas without providing a local service. An interpretative model to support cultural landscape dynamics within linear infrastructure projects was developed and tested in three Italian transportation infrastructures. The model was based on the analysis of the structure and the generating processes of contemporary cultural landscapes and makes use of criteria and indicators.First published online: 14 May 2013